Production of carrageenan from Malaysian seaweed - Jaswir, Irwandi, Ainur Farhana; Jamal, Parveen (IIUM Press, 2011)
Two major red seawveed species available locally in Malaysia (in the coastal area of Sabah) wvhich are Kappaphycu5 alvarezii and Ellehewna dentieulatum where tested to the effect of alkali treatments on the yield and gel strength (quality) of the carrageenans which were collected from the different coastal areas of Sabah. They were analyzed using different alkali concentrations, temperatures and treatment times. For the screening stage of the agar, all samples were treated at set alkali treatment condition which at KOH concentration (5% w/Y), temperature (85°C) and treatment time (90min). All samples \vere then \vill be subjected to hot water extraction (phosphate buffer solution at pH 7.2) at constant parameter of 95°C temperature and 1 hour extraction time. Carrageenan percentage yields value were for Eucheuma dellticlliatum, 55.9 % yield, Kappaphyclis alvarezii collected from Semporna, 61.5 % yield and Kappaphycus alvarezii collected from Kota Kinabalu, 37.5 % yield. Based on the highest yield of carrageenan, Kappaphyclis alvarezii collected from Semporna been chosen for the next stage of optimization where this species been subjected to different condition of parameters which are KOH concentration (2.0-6.0%), temperature (65-95°C) and treatment time (l0-l20min). The optimal conditions are those providing the highest gel strength (tested by using texture analyzer TA-XT plus). In this stage the highest gel strength \\'as 659.13 g/cm2 at condition of 6% \viv KOH concentration, 80LlC temperature and 65 min extraction time.